Video-Enhanced English Asynchronous Learning; Students' Voice - Faisal Rahman; Nur Rahmadani; Dyan Fitri Nugraha (Pendidikan Bahasa Inggris STKIP Nurul Huda, 2022)
Various studies investigated the use of video material in the English classroom. Several studies also observed the effectiveness of asynchronous learning, especially during the Covid-19 pandemic. Nevertheless, there are limited studies discussing the utilization of video material in asynchronous learning. This is quantitative research designed as a survey to obtain students’ perception of the utilization of video material in English asynchronous learning. This research points out that the students have a positive response to the utilization of video material in English asynchronous learning. They are convinced that English asynchronous learning with video is fun, efficient, effective, enjoyable, and easier to learn. The result also shows that the utilization of video material in English asynchronous learning has several benefits: it increases students’ comprehension of the learning material, increases students’ learning motivation, and helps the students enhance their vocabulary. Eventually, the students believe that the material can be explained well via video.